Money Demand in Indonesia: Does Economic Uncertainty Matter? - Kurniawan, Mahrus Lutfi Adi; A'yun, Indanazulfa Qurrota; Perwithosuci, Winny (Universitas Muhammadiyah Yogyakarta, 2022)
Since the global financial crisis of 2008, there has been a rise in economic uncertainty and money demand research. The money demand is vital in monetary policy, which has implications for the regional economy. This study aims to analyse the money demand in Indonesia in the middle of global economic uncertainty, as well as the contribution of the study, which includes the economic and monetary policy uncertainty in a separate model for an enhanced money demand function. The study used a structural vector autoregressive (SVAR) approach. The results indicate that monetary demand is negatively affected by economic uncertainty. With the development of the financial sector, the impact of economic uncertainty and the unpredictability of US monetary policy drives people to be more cautious, resulting in a movement of